(untitled) - Hartley, James (New York, 2008)
Academic Writing and Publishing will show academics (mainly in the social sciences) how to write and publish research articles. Its aim is to supply examples and brief discussions of recent work in all aspects of the area in short, sharp chapters. It should serve as a handbook for postgraduates and lecturers new to publishing. The book is written in a readable and lively personal style. The advice given is direct and based on up-to-date research that goes beyond that given in current textbooks. For example, the chapter on titles lists different kinds of titles and their purposes not discussed in other texts. The chapter on abstracts instructs the reader on writing structured abstracts from the start.
Viết báo cáo khoa học
Keywords: Academic writing,Viết học thuật,Scholarly publishing.,Xuất bản học thuật.